Thrombosis in Brain Tumors - Jo, Jasmin T.; Schiff, David; Perry, James R. (Seminars in Thrombosis and Hemostasis, 2014)
Venous thromboembolism (VTE) is common in patients with brain tumors, occurring in up to 30% of patients with high-grade glioma and up to 20% of those with brain metastasis and primary central nervous system (CNS) lymphoma. The risk is correlated with higher grade malignancies and is directly associated with the production of the potent procoagulant, tissue factor (TF). Upregulation of TF influences both the coagulation pathway and oncogenic signaling mechanisms important for cancer progression. The risk of intracranial hemorrhage with the use of anticoagulants complicates the management of VTE in patients with brain tumor. We discuss the recommended anticoagulants used for initial and long-term treatment of established VTE, including unfractionated heparin, low-molecular-weight heparin (LMWH), and warfarin. Therapeutic anticoagulation, particularly LMWH followed by secondary prophylaxis, is generally safe and effective in the treatment of VTE, including patients on antiangiogenic agents. Anticoagulation also reduces the risk of VTE during the perioperative period. However, despite the high risk of VTE throughout the course of disease, present data do not support routine thromboprophylaxis in brain tumor patients. Further investigation regarding the mechanisms underlying the hypercoagulable state of patients with brain tumors and the potential role of the factors and products of thrombogenesis as biomarkers for risk stratification will be useful in identification and management of patients at risk of developing VTE. Novel oral anticoagulants that directly inhibit thrombin such as dabigatran or factor Xa, including rivaroxaban and apixaban have several potential advantages; however, due to limited data in the cancer population, the use of these newer oral anticoagulants is not currently recommended for patients with malignancy and VTE. Recent studies have explored the role of anticoagulants as anticancer agents, which may contribute to cancer treatment in the future.
Keywords: thromboembolism; brain tumors; glioma; tissue factor; bevacizumab